The Effectiveness of Asiatic Acid, Asiaticoside, and Madecassocide in Centella Asiatica, (Linn), Urb. on the Healing Process of Infected Wounds in Experimental Animals: Systematic Literature Review - Kessyy Widowati; Evi Lusiana; Theodorus; Debby Handayati Harahap; Nita Parisa; Abda Arif (Fakultas Kedokteran Universitas Sriwijaya, 2024)
A wound is a condition where body tissue is damaged as a result of sharp objects, chemicals, animal bites, electric shocks, and so on. Good and correct wound management can prevent wounds from becoming infected. In general, for infected wounds, aminoglycoside antibiotic ointments are used which are effective against gram-negative and gram-positive bacteria, such as gentamicin. Where the use of gentamicin ointment is still the